2012
DOI: 10.2320/matertrans.m2012042
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Phase Transformation during Hot-Forging Process of a Powder Metallurgy α+β Titanium Alloy

Abstract: Dynamic phase transformation during subtransus forging was investigated in a powder metallurgy (PM) Ti1.5Fe2.25Mo alloy. The results show that compressive deformation restrains the hcp (¡)¼bcc (¢) phase transformation, and induces a local martensitic transformation in the deformed sample during subsequent cooling. Thermodynamic analysis confirms the feasibility of these transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[ 1,2 ] The optimization of their properties by tuning the chemical composition (dictating both the β‐transus and the martensite start, M s , temperatures) and the hot deformation conditions, in particular the strain rate and the deformation temperature with respect to the β‐transus temperature, has been an active research topic for several decades, [ 3–6 ] in particular for dual‐phase alloys. [ 7,8 ] The deformation mechanisms and microstructural evolutions of existing commercial dual‐phase titanium alloys are relatively well documented. [ 9 ] Gupta et al have studied the evolution of microstructure and texture in Ti‐15V‐3Cr‐3Sn‐3Al alloy during cold‐rolling and cross‐rolling; it was found that the strain path has a strong effect on the deformation microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] The optimization of their properties by tuning the chemical composition (dictating both the β‐transus and the martensite start, M s , temperatures) and the hot deformation conditions, in particular the strain rate and the deformation temperature with respect to the β‐transus temperature, has been an active research topic for several decades, [ 3–6 ] in particular for dual‐phase alloys. [ 7,8 ] The deformation mechanisms and microstructural evolutions of existing commercial dual‐phase titanium alloys are relatively well documented. [ 9 ] Gupta et al have studied the evolution of microstructure and texture in Ti‐15V‐3Cr‐3Sn‐3Al alloy during cold‐rolling and cross‐rolling; it was found that the strain path has a strong effect on the deformation microstructure.…”
Section: Introductionmentioning
confidence: 99%